Using crowdsourced images to study selected cultural ecosystem services and their relationships with species richness and carbon sequestration - Lee, Heera; Seo, Bumsuk; Cord, Anna F.; Volk, Martin; Lautenbach, Sven (Ecosystem Services, 2022)
Due to the difficulty of capturing spatially explicit information on cultural ecosystem services (CES), previous studies have paid less attention to their relationships with other services. In this study, we quantified the relationships between selected CES using crowdsourced photographs, carbon storage and species richness of plants and butterflies for a case study in Saxony, Germany. The relationships were quantified based on the mutual information metric and using principal component analysis. We further conducted a regression analysis to control for environmental and infrastructure factors such as the share of land use classes, landscape diversity and the presence of viewpoints and picnic sites. Our results showed overall positive relationships between CES indicators and carbon sequestration as well as species richness. However, the magnitude of the relationships varied: the CES indicators showed a stronger relationship with butterfly species richness than with plant species richness. Both CES indicators showed the strongest positive relationship with carbon sequestration. This positive relationship was likely driven by forest cover, which was strongly associated with carbon storage. However, our regression analysis also showed that too much forest cover reduces the perceived CES, in particular for landscape aesthetics. Our findings provide additional information for spatial planning in the study region.